2015
DOI: 10.1063/1.4918980
|View full text |Cite
|
Sign up to set email alerts
|

From photoelectron detachment spectra of BrHBr−, BrDBr− and IHI−, IDI− to vibrational bonding of BrMuBr and IMuI

Abstract: Photoelectron detachment XLX(-)(00(0)0) + hν → XLX(vib) + e(-) + KER (X = Br or I, L = H or D) at sufficiently low temperatures photoionizes linear dihalogen anions XLX(-) in the vibrational ground state (v1v2 (l)v3 = 00(0)0) and prepares the neutral radicals XLX(vib) in vibrational states (vib). At the same time, part of the photon energy (hν) is converted into kinetic energy release (KER) of the electron [R. B. Metz, S. E. Bradforth, and D. M. Neumark, Adv. Chem. Phys. 81, 1 (1992)]. The process may be descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…Very recently, we have developed the ground-state potential energy surface for the I + HI reaction including the spin-orbit interaction and used it to simulate the photodetachment spectra of the IHI À and IDI À anions as well as the vibrational bonding phenomenon in IMuI [43]. We found that the simulated spectra were generally in good agreement with the experimentally observed spectra although the agreement becomes somewhat worse at a higher energy region.…”
Section: Introductionsupporting
confidence: 59%
See 4 more Smart Citations
“…Very recently, we have developed the ground-state potential energy surface for the I + HI reaction including the spin-orbit interaction and used it to simulate the photodetachment spectra of the IHI À and IDI À anions as well as the vibrational bonding phenomenon in IMuI [43]. We found that the simulated spectra were generally in good agreement with the experimentally observed spectra although the agreement becomes somewhat worse at a higher energy region.…”
Section: Introductionsupporting
confidence: 59%
“…These simulated spectra were calculated from the wave packet dynamics calculations on the ground-state potential energy surface. For the calculated spectra, both high-and low-resolution (0.6 and 13 meV) spectra are shown, which are obtained from the calculated autocorrelation functions by multiplying by an appropriate Gaussian damping function exp(Àt 2 /a 2 ) [43,50]. The experimental energy resolutions are reported to be 1-2 and >8 meV for high-and low-resolution spectra, respectively [17,19,23].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations